Edge Transitive Dihedral Covers of The Heawood Graph - Laleh Pourmokhtar; Mehdi Alaeiyan (Journal of the Indonesian Mathematical Society, 2018)
A regular cover of a connected graph is called dihedral ifits transformation group is dihedral. In this paper, the authors clas-sify all dihedral coverings of the Heawood graph whose fibre-preservingautomorphism subgroups act edge-transitively.